UJI PERFORMANSI EVAPORATIVE COOLING SYSTEM PADA KUMBUNG JAMUR MERANG DENGAN VARIASI TEKANANNYA - Ahmad Maulana Kartika; Sunanto Sunanto; Ade Suryatman Margana (Jurnal Teknologi Terapan, 2022)
The mushroom cultivation process carried out by farmers is usually in a kumbung measuring 7 meters long, 5 meters wide, and about 3 meters high. According to farmers' confessions, during the dry season or when the weather is sunny (daytime conditions) the temperatur inside the kumbung is relatively high and can reach temperatures of up to 40 oC. These conditions are clearly not in accordance with the optimum conditions of mushroom growth, where the optimum temperature of the mushroom growth ranges from 30 oC - 35 oC. For this reason, it is necessary to apply an air conditioning system in the mushroom room so that its growth can be optimally as expected. The method used to cool the mushroom room is to use high-pressure spray cooling, where the cooling method of the spray cooling is to utilize the evaporative cooling principle of pressurized water spray with the help of a compressor. The water spray pressure in this test will be varied at 5 psi, 10 psi, and 15 psi. From the experiments that have been carried out, the results of the test at a pressure of 5 psi have the highest efficiency, which is about 19,2%, while at a pressure of 10 and 15 psi it has an efficiency of about 34,2 % and 38,7%, respectively. The average room temperature for a pressure of 5 psi is about 34.8 oC, while for a pressure of 10 and 15 psi each has an average room temperature of about 33.7 oC and 33,4 oC. Furthermore, the cost operational for the 5 , 10 , and 15 psi tests have values of about Rp 18.860,- Rp 29.741,- and Rp 40.662,- montly.